Penerapan COBIT pada Analisis Manajemen Risiko pada Sistem Informasi Desa - Farid Arifin; Resad Setyadi (JURIKOM (Jurnal Riset Komputer), 2022)
The Role of Information Systems (IS) in Information Technology Governance (ITG) has an important role in village government institutions. ITG becomes very important by government agencies in discussing the relationship of Information Technology (IT) investment with businesses in every village. The Karangpucung Village Government has problems with population software services for the operational and administrative needs of village government employees. Investment in IT and the best services to access the needs of village employees and the community is an important reference in service with village government businesses. The purpose of this study was to analyze IS risk management in the Karangpucung village government using the Framework Control Objective for Information and Related Technology (COBIT) 4.1. This study uses quantitative research methods by distributing questionnaires to respondents to obtain validity and reliability test data for good results. The results of the analysis show that the growth rate is at level 3. The results of this study refer to how big or small a maturity level is at the Karangpucung deaa office. Based on the calculation table for each level of compliance from level zero to level five, it shows if there are results of maturity levels in each unit. At the maturity level, the risk assessment shows a value of 2.54 which means that the maturity level is at level three, namely the governance process at the Karangpucung Village office is in a condition in the process of being determined by the village office. The defined process has a value meaning at a decisive position in the process stage. This process is the achievement of goals in a much more organized manner using organizational assets and is well defined. Recommendations from this study are the need to improve network installations in Karangpucung Village and improve administrative software for village and community employees, so that database access can be done quickly so as to facilitate the process of making citizens' correspondence and speed up other services at the Karangpucung Village office